Beta-hydroxybutyrate, an endogenic NLRP3 inflammasome inhibitor, attenuates stress-induced behavioral and inflammatory responses - Takehiko Yamanashi (Nature Portfolio, 2017)
Abstract Neuro-inflammation has been shown to play a critical role in the development of depression. Beta-hydroxybutyrate (BHB) is a ketone body and has recently been reported to exert anti-inflammatory effects via inhibition of NLRP3 inflammasome. Here, we investigated the potential antidepressant and anti-inflammatory effects of BHB on rats exposed to acute and chronic stress. We examined the influence of repeated BHB administration on depressive and anxiety behaviors in a rodent model of chronic unpredictable stress (CUS). Additionally, the influence of acute immobilization (IMM) stress and single BHB administration on hippocampal interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) were assessed. Repeated administration of BHB attenuated CUS-induced depressive- and anxiety-related behaviors. IMM stress increased levels of IL-1β in the hippocampus, while a single pre-administration of BHB attenuated this increase. Although no effect was observed on hippocampal TNF-α levels after 1 h of IMM stress, a single BHB pre-administration reduced hippocampal TNF-α. Our previous report showed that the release of IL-1β and TNF-α caused by stress is tightly regulated by NLRP3 inflammasome. These findings demonstrate that BHB exerts antidepressant-like effects, possibly by inhibiting NLRP3-induced neuro-inflammation in the hippocampus, and that BHB may be a novel therapeutic candidate for the treatment of stress-related mood disorders.